Retinitis Pigmentosa with a Bilateral Coats-Like Response – An Unusual Presentation: Doi: 10.36351/pjo.v40i3.1773 - Sivaranjani; Singh, Deeksha; Jayanth, Arun; D Sindal, Manavi (Pakistan Journal of Ophthalmology, 2024)
Retinitis pigmentosa (RP) is an inherited retinal dystrophy that is usually bilateral with a female preponderance. We report a case of a 40-year-old male diagnosed with bilateral retinitis pigmentosa with coats like response. The diagnosis was confirmed based on clinical examination, typical findings on Fundus fluorescein angiography (FFA), Optical coherence tomography, B-scan and Indocyanine green angiography. Based on angiography findings, in both the eyes of our patient cryotherapy was done to the leaking telangiectatic vessels in the peripheral retina. On follow up, regression of the telangiectatic vessels was noted.